Adulteração de suplementos alimentares comercializados para a perda de peso - Ribeiro, Sandra Maria (2019)
Fat burners are dietary supplements used intentionally to promote weight loss, stimulating lipolysis or inhibiting lipogenesis. The great investment of the media, coupled with the search for a perfect body, has led to a massive consumption of these products. Open access to pharmacies, shops and even the e-commerces makes them easier to import, market and consume. Because of the huge growth of this market, new products are launched, often without due proof of efficacy and safety, which may lead to fraud or adulteration. Given this, there is a need for rapid analytical methods, sensitive and selective analysis of these products. Considering this, this work proposed the development of two analytical methods in HPLC DAD. The first method proposed the determination of caffeine in oily matrices in food supplements. High performance liquid chromatographic separation was achieved using a C18 reversed phase, a binary mixture of a 0.1% phosphoric and acetonitrile with a flow rate of 0.8 mL.min-1. UV detection was 220 nm. Water produced the best extraction efficiency in comparison with other solvents. Retention time observed for caffeine was 4.5 min. The second proposed the development of an analytical method for the determination of 11 adulterants (stimulants, anorectic, antidepressants, antiepileptic, diuretics and laxatives). The chromatographic analysis were conduced at temperature de 35ºC±1ºC using a reversed- phase C18 column, mobile phase gradient was a composed of ammonium acetate 100 mmol.L-1 (pH 5.2), acetonitrile and tetrahydrofuran, flux rate: 1.0 mL.min-1 and UV detection was 224, 250 e 270 nm. A 13 minutes chromatographic run was able to separate all adulterants. anfepramone, caffeine, lamotrigine, bupropion, phenolphtalein, fluoxetine, sertraline, furosemide, bisacodyl, hydroclorotiazide and sibutramine were simultaneously analysed in all samples (n=30). One sample was adulterated with the diuretic furosemide. Both methods were quick, sensible, selective and reproducible in the proposed linear range. The caffeine method to be analytical tool applicable to the oily capsules analysis in time release dietary supplements and the development simultaneous method to be analytical tool applicable to the screening of adulteration of supplements used as fat burners.